Pseudocyst of Auricle—An Uncommon Condition and Novel Approach for Management - Agrawal, Priya U. (Indian Dermatol Online J, 2020)
Pseudocyst of the auricle is a rare benign condition due to the accumulation of intracartilaginous fluid. Various treatment modalities are suggested in literature; the goal being the preservation of architecture of the pinna and prevention of recurrence. We report two cases: An 11-year-old boy treated conventionally with surgical management with the development of mild deformity and an 18-year old male treated with novel nonsurgical modality with the excellent cosmetic result. Here we emphasize the importance of such a simple routine procedure, which can be done on an OPD basis with a better cosmetic outcome.